BIOPSIA DE ENCIA EN EL DIAGNOSTICO DE LA MICROANGIOPATIA DIABETICA - Vega, L. (1999)
A study was made of gingival biopsies perfomed in 42 patients, 24 of the patients. Were diabetics and 18 were non diabeties used as controls. Capillary lesions were found in all diabetic patients. These lesions varied from a minimal thickening of the basement membrane. This thickening was P.A.S. positive. In 90% of the diabetic patients a thickening of the nodular type in the walls of the thickened capillaries and too were fonud a series of pictures of transition between the diffuse, more or less irregular thickening and the appearance of these modular images was noticed; these lesions showed an irregular eosinophilia. The stains used showed that these nodular formations react in the same way as the nodular lesions of the diabetic glomerulies. The authours consider these gingival lesions another manifestation of the generalized vascular damage which is thought to be to the same pathogenic mechanism and to be another manifestation of diabetic microangyopathy.